Psychosocial interventions for perinatal common mental disorders delivered by providers who are not mental health specialists in low- and middle-income countries: a systematic review and meta-analysis. - Kelly Clarke; Michael King; Audrey Prost (PLoS Medicine)
Background Perinatal common mental disorders (PCMDs) are a major cause of disability among women. Psychosocial interventions are one approach to reduce the burden of PCMDs. Working with care providers who are not mental health specialists, in the community or in antenatal health care facilities, can expand access to these interventions in low-resource settings. We assessed effects of such interventions compared to usual perinatal care, as well as effects of interventions based on intervention type, delivery method, and timing. Methods and findings We conducted a systematic review, meta-analysis, and meta-regression. We searched databases including Embase and the Global Health Library (up to 7 July 2013) for randomized and non-randomized trials of psychosocial interventions delivered by non-specialist mental health care providers in community settings and antenatal health care facilities in low- and middle-income countries. We pooled outcomes from ten trials for 18,738 participants. Interventions led to an overall reduction in PCMDs compared to usual care when using continuous data for PCMD symptomatology (effect size [ES] -0.34; 95% CI -0.53, -0.16) but not binary categorizations for presence or absence of PCMDs (OR 0.62, 95% CI 0.35, 1.080 [corrected]. We found a significantly larger ES for psychological interventions (three studies; ES -0.46; 95% CI -0.58, -0.33) than for health promotion interventions (seven studies; ES -0.15; 95% CI -0.27, -0.02). Both individual (five studies; ES -0.18; 95% CI -0.34, -0.01) and group (three studies; ES -0.48; 95% CI -0.85, -0.11) interventions were effective compared to usual care, though delivery method was not associated with ES (meta-regression β coefficient -0.11; 95% CI -0.36, 0.14). Combined group and individual interventions (based on two studies) had no benefit compared to usual care, nor did interventions restricted to pregnancy (three studies). Intervention timing was not associated with ES (β 0.16; 95% CI -0.16, 0.49). The small number of trials and heterogeneity of interventions limit our findings. Conclusions Psychosocial interventions delivered by non-specialists are beneficial for PCMDs, especially psychological interventions. Research is needed on interventions in low-income countries, treatment versus preventive approaches, and cost-effectiveness. Please see later in the article for the Editors' Summary.